GERAKAN FILANTROPI ISLAM PERAN LAZISMU DALAM PEMBERDAYAAN EKONOMI MASYARAKAT KECAMATAN GAMPING KABUPATEN SLEMAN - Prasetyo Rakhmadi, Herlambang Dwi (Universitas Cokroaminoto Yogyakarta, 2021)
Unemployment and poverty are social problems that require immediate resolution. There needs to be a role for organizations outside the government because the government alone is not enough to solve this problem. Lazismu Gamping as a philanthropic institution tries to play a role in overcoming these social problems through empowerment activities using zakat funds. The development of Lazismu Gamping as a philanthropic institution has also changed program policies. Zakat is not only used as a charity fund but is also realized in the financing of community empowerment programs, namely Baitul Tamwil Muhammadiyah (BTM) Surya, Surya Gamping Iron Shop, waste transportation management, PKU Gamping parking and canteen management, and goat farming. This study is intended to determine the role of Lazismu Gamping in the economic empowerment of the Gamping community. The research conducted at Lazismu Gamping was analyzed using the theory of philanthropic activity initiated by Helmut K. Anheier and Diana Leat and the empowerment paradigm of Edi Suharto. This research uses qualitative method with descriptive analytical research type. Data collection methods are observation, in-depth interviews, and documentation. The analytical method used is the Miles and Huberman model in the form of data reduction, data presentation, and conclusions. The results of this study state that Lazismu Gamping as a creative philanthropic institution uses innovative and creative programs through several roles, namely the role of eradicating poverty, the role of empowerment, and the role of education and health insurance. Lazismu Gamping has also succeeded in dealing with social problems, namely poverty with empowerment programs as a manifestation as a philanthropic institution that truly eradicates poverty and improves the welfare of the community.